Peer Influence and Adolescent Sexual Behavior Trajectories: Links to Sexual Initation - Peҫi, Blerta (European Journal of Multidisciplinary Studies, 2017)
This study aims to revisit the studies reported in the area of peer influence with reference to health behavior. Peer groups are social groups that consist of people of the same age and have similar interests and usually equal in terms of the education and social class. Peer groups are important as they tend to provide a space to make friends. They also help provide social and emotional support as well as an identity and a sense of belongingness to a social group, especially during adolescence. The authors have found that sexual behavior is one of the many areas in which teens are influenced by their best friends and peers. Teens are more likely to have sex if their best friends and peers are older, use alcohol or drugs, or engage in other negative behavior. Similarly, they are more likely to have sex if they believe their friends have more positive attitudes toward childbearing, have permissive values about sex, or are actually having sex. The authors have found that most of the studies in this area have been developed have been assessing the negative aspects of peer influence. Understanding important factors related to sexual behavior is important not only to change that behavior; it is important to identify those teens who are most at risk of having sex and unprotected sex. This paper explains the implications for those working to help youth avoid risky sexual behaviors and potential consequences. It is concluded with the recommendations for conducting studies in this direction.
Keywords: peer influence, sexual intercourse, health, adolescent